ATOMIC EMISSION METHOD WITH INDUCTIVELY COUPLED PLASMA FOR DETERMINING OF NOBLE METALS (Au, Ag) IN SAMPLES OF INDUSTRIAL BLISTER COPPER - Roza Ablakimovna Aubakirova; Zhanat Kairollinovna Shomanova; Ruslan Zairovich Safarov; Emin Atasoy (Academic Scientific Journal of Chemistry, 2019)
In the article weare presenting the results of investigation of AES ISP method for Au and Ag determination in samples of industrial blister copper. The developed method allows determining Au in the range 28- 56 g/ton, Ag – 2000-3000 g/ton. Control of precision was conducted using control analytical method (assaygravimetric) as well as using measurement of state standard sample of copper content with attested values of impurities. The developed method is not inferior in metrological characteristics to control analytical method. Optimal spectral lines for Au – 242,795 nm and for Ag – 328,068 nm were selected because they have the most sensitivity and do not have spectral noises. Statistical processing of calibration characteristics for AES ISP determination of Ag and Au was conducted in accordance to RIS 54-2002. As a result, values of average standard relative deviations, the ratio of the average squared deviations and quantile of distribution were obtained. Parameters of precision, correctness, repeatability, reproducibility of the method were calculated according to RIS 61-2013.